2007
DOI: 10.1111/j.1553-2712.2007.tb00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Community-associated Methicillin-resistant Staphylococcus aureus among All Skin and Soft-tissue Infections in Two Geographically Distant Pediatric Emergency Departments

Abstract: Objectives To describe the culture results of cutaneous infections affecting otherwise healthy children presenting to two pediatric emergency departments (EDs) in the southeastern United States and southern California. Methods Medical records of 920 children who presented to the pediatric EDs with skin infections and abscesses (International Classification of Diseases, Ninth Revision codes 680.0–686.9) during 2003 were reviewed. Chronically ill children with previously described risk factors for community‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
1
19
0
2
Order By: Relevance
“…This report supports the suggestion that aggressive antistaphylococcal therapy should be initiated in critically ill patients with suspected MRSA infection and shifted to less aggressive therapy as soon as culture results are obtained and MRSA is excluded [16]. CA-MRSA is usually associated with soft tissue superficial infections [14]; however, it may cause invasive and severe infections and even deaths in previously healthy children [5,12]. Admissions to a Pediatric Intensive Care Unit (PICU) in the USA due to multifocal invasive CA-MRSA infections were increased during 2002-2004 compared to previous years [12].…”
Section: Discussionsupporting
confidence: 79%
“…This report supports the suggestion that aggressive antistaphylococcal therapy should be initiated in critically ill patients with suspected MRSA infection and shifted to less aggressive therapy as soon as culture results are obtained and MRSA is excluded [16]. CA-MRSA is usually associated with soft tissue superficial infections [14]; however, it may cause invasive and severe infections and even deaths in previously healthy children [5,12]. Admissions to a Pediatric Intensive Care Unit (PICU) in the USA due to multifocal invasive CA-MRSA infections were increased during 2002-2004 compared to previous years [12].…”
Section: Discussionsupporting
confidence: 79%
“…Recent data from EDs around the United States have suggested that MRSA is the most common pathogen isolated from SSTIs (11,12). Although there have been several recent reports looking at the epidemiology of MRSA in the tertiary universityaffiliated ED setting, there are limited data looking at the prevalence of MRSA in the community hospital setting in children.…”
Section: Introductionmentioning
confidence: 98%
“…Overall, the incidence of skin and soft tissue infections in US emergency departments has tripled from 1993 to 2005 and now exceeds 3.4 million cases annually [1]. With the recent spread of community-acquired methicillin-resistant staphylococcus aureus (ca-MRSA), communities report prevalence rates of 53% to 80% for these drug-resistant organisms [2][3][4]. With so much effort being spent on producing more antibiotics, little resources are utilized to better treat skin abscesses.…”
Section: Introductionmentioning
confidence: 99%